2022
DOI: 10.1007/s00167-022-06915-6
|View full text |Cite
|
Sign up to set email alerts
|

Consistent indications, targets and techniques for double-level osteotomy of the knee: a systematic review

Abstract: PurposeTo systematically review and critically appraise the literature on double‐level osteotomy (DLO) of the knee, and determine the indications, contraindications, targets and outcomes. Materials and methodsA systematic literature search was performed on PubMed, Embase®, and Cochrane for studies that reported on DLO by any technique or approach, including indications, contraindications, and targets for DLO, as well as patient‐reported outcome measures (pROMS) and radiographic angles. ResultsTwelve eligible s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 21 publications
1
10
0
Order By: Relevance
“…In contrast to the previous studies reporting unfavorable outcome of isolated HTO performed for this group of knees [30,39,42], the present study showed that DLO could yield significant clinical/radiological improvements even for advanced osteoarthritic knees. Consequently, the results of this study support the efficacy and validity of our surgical strategy of anatomical reconstruction of the bone and joint geometry via DLO [5,7,15,27,38]. In recent years, the surgical procedure for DLO has evolved to incorporate biplanar osteotomy and minimally invasive plate osteoosynthesis (MIPO) techniques [10,27,38], and the results have been reported in several studies [10,27,38].…”
Section: Discussionsupporting
confidence: 69%
“…In contrast to the previous studies reporting unfavorable outcome of isolated HTO performed for this group of knees [30,39,42], the present study showed that DLO could yield significant clinical/radiological improvements even for advanced osteoarthritic knees. Consequently, the results of this study support the efficacy and validity of our surgical strategy of anatomical reconstruction of the bone and joint geometry via DLO [5,7,15,27,38]. In recent years, the surgical procedure for DLO has evolved to incorporate biplanar osteotomy and minimally invasive plate osteoosynthesis (MIPO) techniques [10,27,38], and the results have been reported in several studies [10,27,38].…”
Section: Discussionsupporting
confidence: 69%
“…This is a novel study. In a recent systematic review by Alves et al [12] on double‐level knee osteotomies, the 12 included studies reported on DLO which was performed by medial opening‐wedge tibial osteotomy and lateral closing‐wedge femoral osteotomy for varus knees. This is the first study to report on double‐level medial closing wedge osteotomies to correct bifocal valgus knee deformity.…”
Section: Discussionmentioning
confidence: 99%
“…In cases of valgus knees, the distal femur and proximal tibia have to be thoroughly assessed preoperatively to determine the site of the deformity and consider a single-or double-level osteotomy (DLO). This latter allows the achievement of a neutral lower extremity alignment while preventing JLO [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…Measuring these angles together helps us determine the necessary surgical approach (total knee arthroplasty, distal femoral osteotomy, high tibial osteotomy, etc.) [3] needed to correct the malignments by immediately identifying whether the patient’s varus or valgus deformity is derived from femur or tibia [17, 21, 25]. In addition, by monitoring changes in measured angles, the rate of malalignment progression can be determined and the prognosis inferred [7].…”
Section: Discussionmentioning
confidence: 99%